Characterization and suppression of stripe artifact in velocity‐selective magnetization‐prepared unenhanced MR angiography. Issue 5 (13th March 2018) - Shin, Taehoon; Qin, Qin
Abstract : Purpose: To characterize and suppress stripe artifact associated with velocity‐selective (VS) magnetization for unenhanced MRA. Methods: Extended phase graph formalism was used to show that the stripe artifact contains multiples of the fundamental frequency that is determined by the area of unipolar VS gradient. Four VS preparation pulses whose excitation profiles are spatially shifted by quarter the fundamental period of the stripes, were applied alternately. For further suppression of the artifact, k‐space data at kz = 0 were averaged over the 4 VS preparations. The proposed schemes were tested in a chicken breast phantom and healthy human subjects. Results: When the standard VS preparation scheme was used, stripe artifact was shown in all the reconstructed images and appeared as artifactual peaks in k‐space that corresponded to the first and second order harmonics of the fundamental frequency. Alternate application of the 4 phase‐shifted VS preparation pulses suppressed the stripes, but not completely, as evidenced by residual erroneous peaks in k‐space. After the k‐space averaging, the stripe artifact was nearly eliminated. Conclusion: Stripe artifact in VS‐MRA consists of multiples of the fundamental frequency and can be effectively suppressed through alternate application of phase‐shifted VS preparations along with k‐space averaging.